Síntese e caracterização de partículas de acetato de celulose, a partir do caroço de manga, para produção de matrizes de liberação controlada de drogas - Cruz, Alisson Costa da (2010)
In this work the cellulose acetate produced from cellulose fibers of the mango seed was used as a matrix for production of microparticles processed using the method of solvent evaporation. Empty microparticles and loaded paracetamol particles were produced to evaluate the incorporation of an active agent by the polymer during the formation of microparticles. The characterization of the systems produced was done by Infrared spectroscopy (IR), Differential Scanning Calorimetry (DSC) and scanning electron microscopy (SEM). The use of cellulose diacetate as a matrix for production of microparticles led to incorporation of paracetamol observed through an endothermic peak of melting of paracetamol in the DSC thermogram. The particles produced are mostly irregular with few average size of 3μm, the bulk of the material has a fibrous structure without particle production. For cellulose triacetate was observe the formation of spherical and well shaped microparticle with a diameter of 1μm. The incorporation of paracetamol can be confirmed from changes in the pattern of several bands in the infrared region and change the value of the glass transition temperature (Tg) a fact which indicates the existence of interactions between the matrix and the drug incorporated. Quantitatively, there is an incorporation of 1.58% for paracetamol, with a release of 54.8% of the drug after 60 minutes of hydrolysis. The results indicate the feasibility of producing microparticles matrices for incorporation of drugs from renewable cellulosic alternatives